Fetal growth according to maternal parity, height and origin, and fetal sex of Peruvian newborns - Ticona Rendón, Manuel (2015)
Objective: To determine fetal growth according to maternal parity, height and origin, and newborn’s sex. Design: Prospective, transversal study. Setting: Peruvian Ministry of Health hospitals. Participants: Live newborns. Interventions: Enrolment of successive live newborns (LNB) without intrauterine growth restriction in 29 Peruvian Ministry of Health hospitals during 2005. We compared male and female LNB average weights -children from either primiparae or multiparae born in the coast, mountains and jungles-, by student t, considering significant differences when p < 0,05. Maternal height was correlated with LNB’s weight, height, cephalic perimeter and gestational age. Main outcome measures: Influence of fetal sex, maternal parity, height and natural region on intrauterine growth curves. Results: Selected 50 568 LNB males presented average weight 19 to 41 g higher than females and multiparae children were 22 to 53 g higher than primiparae’s. Maternal height had direct relation with LNB weight, height and cephalic perimeter (p < 0,01). Coast newborns weighed 133 to 210 g more than those born in the mountains, and 76 to 142 g more than those born in the jungles; average newborn weights in the jungles were 19 to 83 g above those from those born in the mountains. Differences by sex, maternal parity, height and origin were significant between 36 and 42 weeks of gestation. Conclusions: Birth weight varied according to fetal sex, maternal parity, height and origin. We recommend the use of these differences as adjustment factors factors for an adequate classification of Peruvian newborns according to weight-gestational age.